Displacement patterns of Nellore cattle in integrated crop livestock system - Santana, E. A.R. [UNESP]; Andrighetto, C. [UNESP]; Mateus, G. P.; Aranha, A. S. [UNESP]; Lupatini, G. C. [UNESP]; Meirelles, P. R.L. [UNESP]; Aranha, H. S. [UNESP]; Santos, J. M.F. [UNESP]; Luz, P. A.C. [UNESP]; Trivelin, G. A. [UNESP] (FapUNIFESP (SciELO), 2019)
The objective of this study was to characterize the displacement patterns of Nellore cattle in areas of crop livestock and crop livestock forest integration systems with density of 196 and 448 eucalyptus ha -1 . Paddock maps were drawn from satellite images of the experimental area. In each evaluated system there was one trained observer, that on the paddock map recorded the place the animals stayed every 10 minutes. The exploration of the area by the animals was observed for 12 hours, starting at 6 a.m. and ending at 6 p.m. The displacement of the animals in the ILP system during the evaluation was bigger than the ILPFs systems, resulting in greater exploration of the area, this fact was due the presence of trees that, for the animals resembled fences, limiting the exploration of the paddock in ILPFs. In the ILPF with higher density of trees, this behavior was more evident. In the period from 10:10 a.m. to 14:00 p.m. the displacement of the animals was decrease by the high temperatures in all systems, although it was more effective in the ILP system. It is concluded that the displacement of cattle is influenced by the presence and density of arboreal component integrated crop livestock system.
Padrão de deslocamento de bovinos Nelore em sistemas integrados de produção agropecuária
Keywords: Cattle behavior; Comportamento de gado; Condicionador de pastagem; Crop-livestock-forest integration; Eucalipto; Eucalyptus; Grazing conditioner; Integração de pecuária-floresta